2019
DOI: 10.1177/1948550619862261
|View full text |Cite
|
Sign up to set email alerts
|

All Things Being Equal: Distinguishing Proportionality and Equity in Moral Reasoning

Abstract: Moral foundations theory (MFT) has been a useful framework for understanding moral judgment and its relationship to political leaning. However, some have argued that MFT omits key domains of moral reasoning. We explored the utility of two candidate foundations (Proportionality and Equity) with a national sample of U.S. adults recruited through Nielsen’s Harris Panel, randomly split into calibration ( n = 1,499) and replication samples ( n = 1,499). We find that Proportionality and Equity are conceptually disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 44 publications
(59 reference statements)
2
19
0
Order By: Relevance
“…We were confident in the approach as the same equity-based messages resonated well across political ideologies in the general public study just conducted. We also thought this recent outcome particularly compelling as previous work had found that the value of equity resonated more strongly on the ideological left than right (Skurka et al, 2019). The present study may reflect that earlier pattern of value polarization, given this effect was not observed with these same messages in our more recent general public work.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…We were confident in the approach as the same equity-based messages resonated well across political ideologies in the general public study just conducted. We also thought this recent outcome particularly compelling as previous work had found that the value of equity resonated more strongly on the ideological left than right (Skurka et al, 2019). The present study may reflect that earlier pattern of value polarization, given this effect was not observed with these same messages in our more recent general public work.…”
Section: Discussionsupporting
confidence: 70%
“…Based on our prior work (Skurka et al, 2019;Skurka et al, 2020) and the political reality that many state policy issues have the potential for polarization among office holders whose elections are driven by partisan identities and voter preferences, we also explored the roles of party affiliation and fiscal and social ideologies on message effects: RQ1: How will state legislators' political party affiliation influence the message effects hypothesized above? RQ2: How will state legislators' fiscal and social ideologies influence the message effects hypothesized above?…”
Section: Hypothesis 4 (H4)mentioning
confidence: 99%
“…Each of the messages further emphasized the need to invest more in communities that are starting with the least—thus emphasizing the value of equity. However, we avoided explicit use of the term “equity,” in an attempt to evade the strong political polarization associated with messages that explicitly articulate this value 66 …”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, fairness is also a core moral value (Graham et al, 2009), a value associated with prosocial choices even when analyses control for gender, religiosity, and political ideology (Niemi & Young, 2013). More recent work has also illuminated the moral importance of equity, which is focused on achieving common levels of outcomes at a population level rather than focusing only on equality at an interpersonal level (Skurka et al, 2020). In some cases, people are even willing to behave dishonestly and lose financial rewards in order to maintain equity (Gino & Pierce, 2009).…”
Section: Empathy-induced Immoralitymentioning
confidence: 99%